Pengaruh Kearifan Lokal dan Kecerdasan Spiritual terhadap Perilaku Peserta Didik - Kusno Setiadi (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2019)
This article aims to reveal the influence of local wisdom and spiritual intelligence on the behavior of students in Kabila 1 Public High School. Assessment is carried out with quantitative approaches and survey methods. The data analysis technique used is the analysis of the product moment correlation coefficient and multiple linear regression. The results of the study indicate that: (1) there is a significant influence between local wisdom on student behavior, and the correlation of determination is 17.9%. (2) there is a strong influence between spiritual intelligence on students' behavior and the correlation of determination is 50.8%. (3) there is a strong influence between local wisdom and spiritual intelligence together on student behavior and the correlation of determination is 50.41%. Furthermore, 49.59% of the students' good behavior is influenced by other factors. This is what causes the Kabila 1 Public High School to implement local wisdom-based education and provide spiritual activities in schools in order to cope with the bad behavior of students.